(untitled) - Gray, Tara (Upper Saddle River, 2005)
This series is ideal for any course that includes desktop publishing and/or web design software applications as well as web scripting languages. Courses can be found in Computer Information Systems, Computer Science, and Fine Arts Departments, as well as Continuing Education, and Journalism. Written by educators, for educators, the Essentials for Design series is the complete solution for desktop publishing and/or web design courses. The hands-on, skills-based texts are packaged with resource CD-ROMs that contain all the files needed to create the step-by-step exercises in the text. Instructor Resource CD-ROMs include assessments, PowerPoint presentation materials, and additional projects
Keywords: Multimedia systems,Director (computer file)